Analysis of the nutritional and antinutritional contents of tubers of Agew potatoes (Plectranthus edulis) grown in the Awi Zone, Amhara regional state of Ethiopia - Misganaw Andualem; Bezuayehu Tadesse; Abebe Bitew; Asmamaw Tesfaw (Food Chemistry Advances)
Plectranthus edulis is one of the most important tuberous plants, is an indigenous plant, and grows in middle- and high-altitude areas. This study investigated the proximate, antinutritional, antioxidant, and mineral compositions of P. edulis (Agew potato) grown in the Dangila, Ankesha, and Banja districts in the Awi zone of the Amhara region, Ethiopia. The proximate composition was determined via the Association of Official Analytical Chemists (AOAC) protocol. The moisture, ash, crude fat, crude protein, crude fiber, carbohydrate, phytate, tannin, TPC, TFC, and DPPH assay results ranged from 70.87 to 74.92 g/100 g, 3.92–4.58 g/10 g, 0.36–0.61 g/100 g, 6.86–9.29 g/100 g, 3.18–3.56 g/100 g, 71.79–78.81 g/100 g, 61.48–108.04 mg/100 g, 8.46–44.15 mg/100 g, 17.53–28.42 mg/g, 2.75–5.71 mg/g, and 52.94–71.49%, respectively. The concentrations of Na, P, Fe, Cu, and Zn ranged from 261.85 to 603.90 mg/kg, 82.02–251.82 mg/100 g, 23.74–65.36 mg/kg, 9.98–16.27 mg/kg, and 17.68–30.20 mg/kg, respectively. The Agew potato from Dangila had a better nutritional content than Banja and Ankesha. Agew potatoes are nutritious and medically important tuber plants used to secure food, especially in undernourished societies.